As Ilhas do Porto Lugares de Resistência - Fátima Loureiro de Matos (2009)
This paper presents an analysis of a group of slum islands (Pt.: ilhas) and other similar housing typologies in the parish of Ramalde in the city of Porto. The study aims to understand why people still live in these houses, whose conditions remain below the minimum standards of comfort and sanitation for a city and a society which should be modern and developed. The introduction examines the characteristics of the ilhas, highlighting their origins, morphology, location, and features of supply, demand and evolution, during the 19th and 20th centuries. Next, the paper will focus on the object of the study, the characterisation of the parish, and the methodology employed in the case study, as well as the portrayal of the housing situation and the population of the ilhas and other similar housing typologies analysed.